2006
DOI: 10.1111/j.1365-2672.2006.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a virulence-associated phenotype after growth of Listeria monocytogenes on food

Abstract: Aim:  To assess the effect of different foods, which have been implicated or not in cases of listeriosis, on the in vitro virulence‐associated phenotype level of different Listeria monocytogenes strains. Methods and Results:  The virulence‐associated phenotype level of L. monocytogenes was studied with the in vitro cell test based on a plaque‐forming assay with a human adenocarcinoma cell line (HT‐29) monolayer. Three strains of L. monocytogenes were grown in preparations (homogenate, 1‐μm filtrate or 0·2‐μm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
13
0
3
Order By: Relevance
“…The importance of extracellular proteins in environmental adaptation has been reported in L. monocytogenes (Midelet-Bourdin et al, 2006;Soni et al, 2011). The temperature of 11°C was chosen as one at which growth is not excessively slow, but also because it is an abusive refrigeration temperature occurring more often than would be expected in the food chain (including in the consumer's home).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of extracellular proteins in environmental adaptation has been reported in L. monocytogenes (Midelet-Bourdin et al, 2006;Soni et al, 2011). The temperature of 11°C was chosen as one at which growth is not excessively slow, but also because it is an abusive refrigeration temperature occurring more often than would be expected in the food chain (including in the consumer's home).…”
Section: Discussionmentioning
confidence: 99%
“…Refrigeration is a widespread process used in the food chain to extend product shelf-life as it is the most common hurdle to microbial growth, but L. monocytogenes is able to grow at low temperatures (Tasara and Stephan, 2006). The bacterium extracellular proteome or exoproteome, an important subset of the total proteome, is marked by its functional nature, undergoing variations and adaptations according to the bacterial surrounding conditions in each moment (Conte et al, 2000;Lee and Schneewind, 2001;Midelet-Bourdin et al, 2006). Altered expression of multiple cytoplasmic proteins was detected in a strain of L. monocytogenes grown at low temperature (Cacace et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Of the six species that comprise the genus Listeria, only L. monocytogenes and L. ivanovii are pathogenic and cause disease, while strains of the species L. innocua, L. welshimeri, L. seeligeri, and L. grayi are generally considered to be nonpathogenic (26). L. monocytogenes is a major foodborne pathogen, and listeriosis is an invasive disease that in its severest form can lead to meningitis, meningoencephalitis, septicemia, and abortions (38). Listeriosis occurs primarily in pregnant women, newborn infants, and the elderly as well as in immunocompromised patients, with a mortality rate of about 30% (22,36).…”
mentioning
confidence: 99%
“…Moreover high virulence in Salmonella typhimurium can be costly in terms of reduced growth in the outside host environment because of the expression of virulence factor (type III secretion system) in a non-host environment [44]. The nutritional conditions of the bacterial growth environment can also significantly affect bacterial metabolism and the expression of virulence factors [45]–[47]. For example, it has been found that the virulence of the pathogenic fungi was negatively correlated to the carbon-to-nitrogen (C∶N) ratio of the culturing medium [48]–[50].…”
Section: Introductionmentioning
confidence: 99%